Analisis Pengaruh Faktor-Faktor Internal terhadap Profitabilitas (Studi Kasus PT. Bank Panin Dubai Syariah Tbk.) - Anisa Herdian; Benny Barnas; Muhamad Umar Mai; Fifi Afiyanti Tripuspitorini (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to determine the internal factors that can affect the profitability of Bank Panin Dubai Syariah. The dependent variable used in this study is profitability which is proxied by Return on Assets. Meanwhile, the independent variables in this study are Capital Adequacy Ratio, Non Performing Financing, Financing to Deposit Ratio, and Operating Income Operating Costs. The data in this study were obtained from the publication of the quarterly financial reports of Panin Dubai Sharia Bank for the period 2011 to 2020 with a total of 40 data. The method used is multiple linear regression analysis and the results show that the Capital Adequacy Ratio has a significant positive effect on Return on Assets, Non-Performing Financing has no effect on Return on Assets, Financing to Deposit Ratio has a significant negative effect on Return on Assets, and Operational Costs have a significant negative effect on Return on Assets.